2006
DOI: 10.1111/j.1439-0531.2006.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding and Reproduction in Endangered Ungulates: Preservation of Genetic Variation through the Organization of Genetic Resource Banks

Abstract: There is a constant increase in the number of species suffering marked reductions in population size. This reduction in size and the lack of genetic flow may lead to a decrease in genetic variability and to matings between close relatives (i.e. inbreeding) with an ensuing reduction in fitness. It is thus important to understand the mechanism underlying the deleterious effects of inbreeding and to develop reproductive biotechnologies that will allow the reduction of inbreeding depression by facilitating gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 85 publications
(177 reference statements)
0
24
0
Order By: Relevance
“…Previous studies have found that, on average, higher levels of inbreeding lead to worse individual body condition (Gomendio et al, 2000;Cassinello et al, 2001;Cassinello, 2005;Roldan et al, 2006). In our populations, the inbreeding coefficient varies widely among individuals in both species studied (Table 1); we can then safely assume that the body condition of the individuals studied would vary accordingly.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have found that, on average, higher levels of inbreeding lead to worse individual body condition (Gomendio et al, 2000;Cassinello et al, 2001;Cassinello, 2005;Roldan et al, 2006). In our populations, the inbreeding coefficient varies widely among individuals in both species studied (Table 1); we can then safely assume that the body condition of the individuals studied would vary accordingly.…”
Section: Discussionmentioning
confidence: 89%
“…In the case of males belonging to endangered species or genetic reserves, every ejaculate needs to be processed for the preparation of frozen ID (Roldan et al 2006). Thus, choosing the most suitable extender for individual stallions is a crucial step (Graham 1996).…”
Section: Discussionmentioning
confidence: 99%
“…comm.). This might be a consequence of pedigree, as Squires (2013) reported the poorest quality in the Friesian, Andalusian, and Saddlebreds; moreover, quite high inbreeding depression in this breed (Vostra-Vydrova et al 2016) might negatively interfere with reproduction (Roldan et al 2006) Even though the cryopreservation process was introduced many years ago, the possibility of increasing effectiveness has been studied intensively across species since that time (Muchlisin et al 2015;Zhang et al 2015). Although our knowledge and techniques for freezing stallion ejaculate have improved within the last 20 years, a considerable proportion of stallions are still not suitable for semen freezing (Katila 2001).…”
mentioning
confidence: 99%
“…The Estación Experimental de Zonas Aridas in Spain, in collaboration with other European institutions, maintains a population of Mohor gazelle (Gazella dama mhorr) and has obtained offspring from artificial insemination [28]. In the near future the program for Dorcas and Mohor gazelles will be enhanced by assisted reproduction techniques [28]. The Scimitar-horned Oryx (Oryx dammah) is another successful example; this species is extinct in the wild, 155 but captive herds are kept in fenced protected areas in Tunisia, Senegal and Morocco as part of longterm reintroduction programs, while the National Zoo in Washington has developed an artificial insemination procedure to preserve its population of Scimitar-horned Oryx and to avoid inbreeding [29].…”
Section: Implications For Conservationmentioning
confidence: 99%
“…Animals are initially kept in enclosures at Guembeul Fauna Reserve and North Ferlo Fauna Reserve, to be later released to the wild [27]. The Estación Experimental de Zonas Aridas in Spain, in collaboration with other European institutions, maintains a population of Mohor gazelle (Gazella dama mhorr) and has obtained offspring from artificial insemination [28]. In the near future the program for Dorcas and Mohor gazelles will be enhanced by assisted reproduction techniques [28].…”
Section: Implications For Conservationmentioning
confidence: 99%